Extraction of polyphenolic antioxidants from orange peel waste using deep eutectic solvents - Ozturk, Baranse; Parkinson, Charles; Gonzalez-Miquel, Maria (Separation and purification technology, 2018)
[Display omitted] •Biorenewable DES efficiently extract polyphenolic antioxidants from orange waste.•ChCl:EG 1:4 provides the highest polyphenolic content and antioxidant potential.•Ferulic acid is the main antioxidant present in the polyphenolic extracts.•Structural analysis suggests DES efficient solvent for biomass pretreatment.•Novel orange waste valorization strategies can be developed based on sustainable DES. Extraction of polyphenolic compounds from orange peel (OP) via solid-liquid extraction (SLE) using deep eutectic solvents (DES) was investigated in this work as a means to develop sustainable separation processes to recover natural antioxidants from food waste biomass. In particular, choline chloride-based DES paired with glycerol and ethylene glycol were explored as potential extractants to evaluate the effect of the solvent structure (i.e. number of hydroxyl groups and hydrogen bond acceptor/donor ratio) on the polyphenol extraction efficiency. Afterwards, the effect of different operating parameters (i.e. solvent concentration, temperature, time and solid/liquid ratio) were further evaluated to determine the optimal extraction conditions for polyphenols recovery in terms of total phenolic content (TPC) and antioxidant activity based on DPPH radical scavenging method. Under optimum conditions (DES 10 wt.% water, temperature of 333.15 K, 1:10 solid/liquid ratio and extraction time of 100 min), choline chloride-based DES outperformed the benchmark solvent (aqueous (aq.) ethanol 30 wt.% water) for the extraction of polyphenolic compounds from OP, with [Ch]Cl:EG 1:4 providing the highest TPC (3.61 mg gallic acid equivalent per gram of orange peel (GAE/g OP) and antioxidant potential (30.6 µg/ml). Although ethylene glycol (EG) has provided the highest TPC (5.84 mg GAE/g OP), DES have proved more selective towards target polyphenolic compounds. Additionally, Scanning Electron Microscopy (SEM) was performed to illustrate the structural modifications occurred on the biomass before and after the extraction process, supporting DES as efficient solvents for cell wall dissolution. Lastly, characterization and quantification of individual polyphenolic profiles in the extracts were completed via high performance liquid chromatography (HPLC), displaying ferulic acid as the most abundant compound followed by ρ-coumaric acid and gallic acid.